Gion Matsuri in Kyoto: A Multilayered Religious Phenomenon - Porcu, Elisabetta (Journal of Religion in Japan, 2020)
In this paper, I analyze Gion Matsuri in Kyoto as a multilayered phenomenon, and explore its religious aspects in context, with particular attention to interactions between actors, such as its organizing bodies, residents of the neighborhoods that sponsor the yama and hoko floats, the local government, and Yasaka Shrine (Yasaka Jinja 八坂神社). Based on my extended fieldwork, I focus on the festival’s most recent transformations (esp. the reinstatement of ato matsuri in 2014) and the negotiation of religious and secular boundaries, both within and without the festival’s physical spaces. I also reflect on Gion Matsuri as a “contested zone,” an idea that contributes to opening up new perspectives for the study of this and other festivals. More broadly, my analysis aims to shed light not only on the multidimensional character of Gion Matsuri, but also on the interplay of religion with different arenas of contemporary society, including local communities and government, tourism, the economy, and cultural policies.